28. STUDY OF CLINICAL AND IMAGING CHARACTERISTICS OF INTERTROCHANTERIC FEMORAL FRACTURES IN ELDERLY PATIENTS WHO UNDERWENT CEMENTLESS PARTIAL HIP REPLACEMENT AT VINH CITY GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Objective: To describe the clinical characteristics and imaging diagnosis of patients with intertrochanteric femur fractures undergoing cementless modular hemiarthroplasty at Vinh City General Hospital. Subjects and methods: A descriptive retrospective and prospective study was conducted on 39 patients who underwent surgery for intertrochanteric femur fractures with cementless modular hemiarthroplasty at Vinh City General Hospital from January 2021 to March 2023. Results: The average age was 84.77 ± 5.90, and the most common age group was 80-89 years old (51.3%). The majority of patients were female, accounting for 82%. The primary cause of the fractures was accidents during daily activities, representing 69.2% of cases. All patients with intertrochanteric femur fractures experienced pain. According to the AO classification, the most common type of intertrochanteric femur fracture observed in X-ray images was type A2, accounting for 51.3%. cardiovascular diseases were the most prevalent among various comorbidities, with a rate of 30.8%. According to the Singh classification, type II osteoporosis was the most common, accounting for 51.3%. Conclusion: Patients with intertrochanteric femur fractures are typically elderly and the primary cause is accidents during daily activities. They may have underlying chronic conditions, especially cardiovascular diseases, along with complex fractures and moderate osteoporosis, which are frequently encountered.
Keywords: Intertrochanteric femur fracture, clinical characteristics, X-ray.